Dental traumatic injuries during the COVID-19 pandemic: A retrospective study - Kotanli, Mehmet Veysel; Doğan, Mehmet Emin; Kotanli, Sedef; Doğan, Mehmet Sinan (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2023)
Background: Although dental trauma has been reported at various frequencies worldwide, as far as we know there are few data regarding the frequency of dental trauma during the pandemic period. Purpose: This study aims to retrospectively evaluate the data of pediatric patients who were admitted to the Department of Pedodontics in a university hospital due to dental trauma during the COVID-19 pandemic. Methods: Between April 2020 and December 2020, the clinical records regarding admissions to the Harran University Faculty of Dentistry Pedodontics clinic due to dental trauma were examined. The age and gender of the patient, type of trauma, teeth affected by the trauma, and treatment methods applied after the trauma were recorded. The data obtained were analyzed using the independent sample t-test for intergroup comparisons and Pearson chi-square test for categorical variables with the help of Statistical Package for the Social Sciences version 23.0. Results: The data of 43 patients (27 males and 16 females) aged between 1–13 years (mean age: 9.13±3.20) who were admitted to the clinic with trauma complaints during an eight-month period were evaluated. It was determined that the most common trauma types in the pandemic period were simple crown fracture (25.6%) and subluxation/lateral luxation (23.3%). During the pandemic, 34.9% of all cases were